Gamified Team Tournaments with QuizWhizzer: Igniting English Learning Outcomes - Satriani; Ammang Latifa; Salasiah Ammade; Rafi’ah Nur (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The study addresses the persistent issue of low student motivation and engagement in English learning, which often leads to suboptimal academic outcomes. To tackle this problem, the research explores the integration of Team Game Tournament (TGT) and QuizWhizzer, combining gamification and collaborative learning strategies. The objective is to evaluate the effectiveness of this method in improving English learning outcomes among junior high school students. A quantitative approach was employed, involving 29 ninth-grade students from UPTD SMPN Satap 9 Barru during the 2024–2025 academic year. Participants were divided into experimental and control groups. The experimental group utilized TGT and QuizWhizzer, while the control group used Quizizz. Pre-test and post-test data were collected, and a t-test analysis was conducted to measure the impact of the intervention. Results demonstrated a significant improvement in the experimental group’s post-test scores, indicating the method’s effectiveness in enhancing student motivation, engagement, and academic performance. The findings suggest that integrating gamification and collaborative strategies can provide an innovative and effective solution to improve learning outcomes in English education.